Integrating Local Environmental Resources into Social Studies Curriculum: A Case Study of Primary Education in Enhancing Environmental Literacy - Maulana, Amri Dhimas; Sapriya, Sapriya; Mansyur, Alif Ilman; Utami, Lingga (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
This study explores how integrating local environmental resources into the social studies curriculum at the primary school level enhances students' environmental literacy. Utilizing a qualitative case study approach, data were collected from 12 teachers, 16 students, and 4 community members through in-depth interviews, participatory observations, and document analysis. Thematic analysis revealed that students' understanding of environmental issues improved through contextual and interdisciplinary learning, supported by community involvement. Despite challenges such as limited resources and teaching materials, the collaboration between teachers and the local community was crucial for successful implementation. The findings highlight the importance of contextualizing environmental education within social studies to foster a deeper connection between students and their local environment, thereby promoting sustainable practices and environmental stewardship. The study underscores the need for tailored strategies and continuous support to address challenges and ensure effective integration of local environmental resources into the curriculum.